Schimmelpenning–Feuerstein–Mims syndrome (a case report) - A. S. Ol’shanskaya; A. V. Dyuzhakova; N. A. Shnayder; D. V. Dmitrenko; T. N. Guzey (Русский журнал детской неврологии)
Linear nevus sebaceous is a rare sporadic neuro-oculocutaneous syndrome characterizes by a triad of symptoms: linear nevus sebaceous, lesion of the central nervous system and lesion of the organs of vision. The authors present a brief overview of Russian and foreign literature and clinical observation of a patient with a specific skin lesion against the background of the congenital Schimmelpenning–Feuerstein–Mims syndrome. The problems of differential diagnostics of the nevus sebaceous of Jadassohn with the syndrome Schimmelpenning–Feuerstein–Mims are analyzed.